Pengaruh Penambahan Tepung Kunyit (Curcuma longa) dalam Ransum Terhadap Performa Produksi Ayam Kampung Super - Harmoko Harmoko; Novi Eka Wati; Muki Suhadi (Fakultas Peternakan Universitas Tulang Bawang Lampung, 2020)
The aim of the study was to know the effect of Curcuma longa as herbal feed additive on feed consumption, daily body weight gain and feed conversion ratio of super native chicken. The research was conducted at Kemukus Village, Ketapang District, South Lampung Regency. The experimental used 80 unisex of super native chicken 5 weeks old. They were feed a ration with control ration + 0% turmeric flour (P0), control ration + 0,04% turmeric flour (P1), control ration + 0,08% turmeric flour (P2) and control ration + 0,12% turmeric flour (P3) during 30 days. The control ration containing 21% crude protein and 3150 kcal/kg metabolism energy. The study used a quantitative metodh with completely randomized design with 4 treatments and 4 replications. The results showed that the addition of turmeric flour (Curcuma longa) up to 0,12% was affected (P <0,05) on feed consumption but did not effect (P> 0,05) on daily body weight gain and feed conversion ratio.Keywords: daily body weight gain, feed consumption, feed conversion ratio, super native chicken, turmeric